Exploring the Nutritional Impact of Sourdough Fermentation: Its Mechanisms and Functional Potential - Alkay, Zuhal; Falah, Fereshteh; Cankurt, Hasan; Dertli, Enes (MDPI, 2024)
Sourdough fermentation is one of the oldest traditional methods in food technology and occurs as a result of fermentation of flour prepared from grains. The nutritional role of sourdough is related to the final composition of fermented foods prepared through sourdough fermentation, and recently, sourdough has become an important application to improve nutrition characteristics of bread. Thanks to lactic acid bacteria (LAB) presented in sourdough microflora and metabolites partially produced by yeasts, technological and important nutritional features of the bread improve and an increase in shelf life is achieved. In addition, sourdough bread has a low glycemic index value, high protein digestibility, high mineral and antioxidant content, and improved dietary fiber composition, making it more attractive for human nutrition compared to regular bread. When the sourdough process is applied, the chemical and physical properties of fibers vary according to the degree of fermentation, revealing the physiological importance of dietary fiber and its importance to humans' large intestine microbiota. Therefore, taking these approach frameworks into consideration, this review highlights the benefits of sourdough fermentation in increasing nutrient availability and contributing positively to support human health.
Keywords: sourdough; microflora; nutritional role; LACTIC-ACID BACTERIA; VITRO STARCH DIGESTIBILITY; IMPROVES POSTPRANDIAL GLUCOSE; PREDICTED GLYCEMIC INDEXES; IRRITABLE-BOWEL-SYNDROME; DIETARY FIBER; GLUTEN-FREE; PHYTASE ACTIVITY; BLOOD-GLUCOSE; WHEAT-FLOUR; Food Science & Technology